Implementation of Sister City Between Jayapura-Vanimo-Wewak Cities as a Model of Paradiplomacy - Pugu, Melyana Ratana; Renyaan, Dorthea (Journal Research of Social Science, Economics, and Management, 2025)
The implementation of the Sister City concept between Jayapura City (Indonesia) and Vanimo and Wewak (Papua New Guinea) has become an important strategy in strengthening cross-border cooperation based on paradiplomacy. Paradiplomacy refers to a form of subnational diplomacy that allows local governments to establish international relations to support economic, social, and cultural development. This study aims to analyze the effectiveness of Sister City implementation between the three cities in improving trade connectivity, cultural exchange, and collaboration in education and health. This study uses a qualitative approach with policy analysis methods, in-depth interviews, and case studies of various Sister City implementations around the world. Data collected through interviews with local stakeholders and policy documents form the basis for developing practical recommendations on improving cooperation between the cities, with a focus on strengthening trade relations and cultural exchange. The results of this study are expected to contribute to the development of more effective bilateral policies, particularly in the context of local governments in both countries. The expected outputs of this study are policy recommendations in the form of policy briefs for Indonesia and Papua New Guinea, as well as publication in a Sinta 2 indexed journal.